Hands free mama : a guide to putting down the phone, burning the to-do list, and letting go of perfection to grasp what really matters! - Stafford, Rachel Macy, 1972- (Zondervan, 2013)
A popular Christian blogger provides a step-by-step guide to transforming a distracted parenting life into one of meaningful connection and fulfillment by learning to grasp and appreciate the moments that really matter.